1993
DOI: 10.1007/bf01658698
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary management of meconium ileus

Abstract: Meconium ileus was noted as an early manifestation of cystic fibrosis in 60 neonates between 1972 and 1991. There were 20 girls and 40 boys. A family history of cystic fibrosis was present in six children. Twenty-five neonates had uncomplicated meconium ileus due to inspissated meconium within the terminal ileum. Thirty-five neonates presented with 56 complications of meconium ileus, including volvulus (n = 22), atresia (n = 20), perforation (n = 6), and giant cystic meconium peritonitis (n = 8). Clinical pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
2
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 52 publications
1
40
2
4
Order By: Relevance
“…The predominant complications of MI were volvulus, gangrene, perforation and atresia seen in both groups. Delphin et al, Rescorla et al and Karimi et al reported similar findings 7,8,12 . Significant differences were found between the types surgical procedures in both groups in this study.…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…The predominant complications of MI were volvulus, gangrene, perforation and atresia seen in both groups. Delphin et al, Rescorla et al and Karimi et al reported similar findings 7,8,12 . Significant differences were found between the types surgical procedures in both groups in this study.…”
Section: Resultsmentioning
confidence: 62%
“…Intra peritoneal leakage was found more in Bishop Koop procedure followed by T tube ileostomy. Delpin et al and Karimi et al mentioned higher risk of leakage in Bishop Koop procedure 8,12 . In Bishop Koop procedure intestinal contents passes into distal bowel, thus more fluid & nutrients are absorbed.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations